P6 Factors associated with HBsAg-positive status in primary care in England: data from the Oxford-Royal College of General Practitioners Research (RCGP) and Surveillance Centre (RSC) network. (28th September 2020) - Villa, Giovanni; Austin, Harrison; Smith, Colette; Lusignan, Simon de; Sherlock, Julian; Ferreira, Filipa; Geretti, Anna Maria
Abstract : Introduction: Mapping the epidemiology of HBV infection informs effective control policies. We report the characteristics of the primary care population with recorded HBsAg-positive status across England. Methods: We retrieved records from people aged ≤80 years held by the RCGP RSC, which collects data from >500 GP practices throughout England. Factors associated with a recorded HBsAg positive result were explored by multivariable logistic regression analysis among all patients recorded in the database between Jan 2008 and Jul 2019. Results: Among 6, 975, 119 patients, 8, 065 (0.12%) had a recorded HBsAg positive status. HBsAg-positive people had a median age of 44 years (IQR 37–54) and 48% were females. Ethnicity comprised 31% white, 25% Asian, 24% black, and 20% mixed/other. Regional breakdown comprised 46% London, 22% South of England, 19% North of England, and 13% Midlands/East Anglia. Table 1 shows factors associated with HBsAg positive status in the whole population. After adjusting for age, gender, ethnicity, and NHS region, the odds of HBsAg positivity were highest among people of non-white ethnicity, cohabitants of HBsAg-positive people, men who have sex with men, injecting drug users, commercial sex workers and people with HIV or HCV. The odds were overall higher in people with a record of STI testing, and a strong independent association was detected between HBsAg positive status and a diagnosis of syphilis. Discussion: The data provide a map of HBsAg-positive primary care populations across England. Among other recognised risk factors for HBV infection, we identified a strong association with a diagnosis of syphilis.